How does market competition affect supplier-induced demand? An experimental study - Chen, Yefeng; Pan, Yiwen; Ding, Yuli (Frontiers in Public Health, 2023)
This paper employs the credence goods framework to investigate the impact of competition on supplier-induced demand, which theoretically derives the predictions of physicians’ behaviors in monopolistic and competitive markets, and we also conduct behavioral experiments to empirically test the hypotheses. The theoretical analysis reveals that an honest equilibrium would not exist in a monopolistic market, whereas price competition can induce physicians to reveal their own types and achieve honesty; thus, the competitive equilibrium is superior to that in a monopolistic market. The experimental results only partially support the theoretical predictions, which show that the cure rate of patients in a competitive environment is higher than that in a monopolistic market, although supplier-induced demand occurs more frequently. In the experiment, the main channel by which competition improves market efficiency is to increase patients’ consultation through low pricing, as opposed to the theory in which competition will lead to physicians’ honest treatment through fair prices. We discover that the divergence between theory and experiment stems from the theory's reliance on the assumption that humans are rational and self-interested, which means that they are not as price-sensitive as predicted by theory.